Pengaruh Kepemilikan Institusional Terhadap Nilai Perusahaan Dimoderasi Oleh Corporate Social Responsibility: - Shabran Jamil; Erinos NR; Mayar Afriyenti (Jurnal Eksplorasi Akuntansi, 2019)
This study aims to find empirical evidence regarding the relationship between institutional ownership and company value which is moderated by corporate social responsibility (CSR). The population in this study were 48 property and real estate companies listed on the Stock Exchange in 2015-2017, with the number of samples used was 35 companies. The data used is secondary data in the form of annual reports obtained from the IDX website (www.idx.co.id). The testing in this study was conducted with moderated regression analysis (MRA). The results show that institutional ownership has no effect on corporate value and Corporate Social Responsibility (CSR) has not been able to moderate the moderation between institutional ownership and firm value.